Non-invasive Brain Stimulation for the Rehabilitation of Children and Adolescents With Neurodevelopmental Disorders: A Systematic Review - Finisguerra, Alessandra; Borgatti, Renato; Urgesi, Cosimo (Frontiers in Psychology, 2019)
In the last years, there has been a growing interest in the application of different non-invasive brain stimulation techniques to induce neuroplasticity and to modulate cognition and behavior in adults. Very recently, different attempts have been made to induce functional plastic changes also in pediatric populations. Importantly, not only sensorimotor processing, but also higher-level functions have been addressed, with the aim to boost rehabilitation in different neurodevelopmental disorders. However, efficacy and safety of using these techniques in pediatric population is still debated. The current article aims to review the non-invasive brain stimulation studies conducted in pediatric populations using Transcranial Magnetic Stimulation or transcranial Direct Current Stimulation, . Specifically, the available proofs concerning the efficacy and safety of these techniques on Autism Spectrum Disorder, Attention Deficit/Hyperactivity Disorder, Dyslexia, Tourette Syndrome and Tic Disorders are systematically reviewed and discussed. The article also aims to provide an overview about other possible applications of these and other stimulation techniques for rehabilitative purposes in children and adolescents.